P241 Is a negative FIT falsely reassuring? A retrospective evaluation. (19th June 2022) - Manning, Sarah; Maxfield, Dominic; Bragg, Rebecca; Gillott, Holly; Clarkson-Cox, Martha; Malik, Imran; Rees, Colin; Neilson, Laura
Abstract : Introduction: FIT (faecal immunochemical test) is recommended by NICE in the assessment of symptomatic patients who do not meet criteria for urgent suspected cancer referral. It can be a useful tool where there is a lower suspicion of cancer and may avoid unnecessary colonoscopies in select cases. However, previous studies report a cancer miss rate of 7-13%. 1 2 The aim of this audit was to identify the number of FIT-negative new colorectal cancer (CRC) cases in a single centre. Methods: This was a single centre, retrospective audit. New CRC cases between June and December 2021 were identified. Bowel cancer screening programme patients were excluded. Where histology was available, adenocarcinomas and polyps with high grade dysplasia were included. If only a radiological diagnosis was available, patients were included if the diagnosis was presumed to be CRC. Neuroendocrine tumours, cancers of non-colorectal primary, lymphomas and anal squamous cell carcinomas were excluded. Data was collected on symptoms, tumour location, histology, metastases and FIT level. A FIT cut off of <10ug/g was used as recommended by NICE. Results: 122 patients were included. 67 of these had FIT tests prior to diagnosis, of which 5 were negative (7.5%). of the FIT negative cases, age ranged from 56-82 and cancer location varied (rectum, splenic flexure, hepatic flexure, ascending colon and caecum). Two patients presented with iron deficiency anaemia and one each with rectal bleeding, weight loss and diarrhoea with weight loss. Conclusions: 7.5% of CRC cases had a negative FIT, which is consistent with previous literature. This adds to the existing body of evidence that a negative FIT does not rule out CRC in symptomatic patients and urgent referral should be offered if red flag features are present. In our series, one patient did not meet NICE criteria for suspected CRC and therefore referral would not have been indicated with a negative FIT. Clinicians must bear this in mind, thoroughly assess risk factors and use clinical judgement when considering whether to refer or investigate. This was a small, single centre audit and further studies with larger data sets are required to accurately assess FIT's sensitivity and specificity. References: Laszlo H.E, et al. Faecal immunochemical test for patients with 'high-risk' bowel symptoms: a large prospective cohort study and updated literature review. Br J Cancer 2021. Farrugia A, et al. Faecal immunochemical testing (FIT) in symptomatic patients: what are we missing? Frontline Gastroenterology 2020.